2010
DOI: 10.1186/1476-4598-9-254
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation in a defined genetic background: proteome changes displayed by 2D-PAGE

Abstract: BackgroundCancer arises from normal cells through the stepwise accumulation of genetic alterations. Cancer development can be studied by direct genetic manipulation within experimental models of tumorigenesis. Thereby, confusion by the genetic heterogeneity of patients can be circumvented. Moreover, identification of the critical changes that convert a pre-malignant cell into a metastatic, therapy resistant tumor cell, however, is one necessary step to develop effective and selective anti-cancer drugs. Thus, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 49 publications
6
32
0
Order By: Relevance
“…It was shown that Prx6 is upregulated in patients with esophageal squamous cell carcinoma [70]. In contrast, previous proteomic analysis using malignant transformative cell models exhibited the downregulation of Prx6 [71]. Our data are similar to those on esophageal squamous cell carcinoma.…”
Section: Prx2supporting
confidence: 83%
“…It was shown that Prx6 is upregulated in patients with esophageal squamous cell carcinoma [70]. In contrast, previous proteomic analysis using malignant transformative cell models exhibited the downregulation of Prx6 [71]. Our data are similar to those on esophageal squamous cell carcinoma.…”
Section: Prx2supporting
confidence: 83%
“…In addition, an extended analysis of protein posttranslational modifications could provide additional insight, especially into the final step of the model, where few genes were differentially expressed. A classical proteomics strategy based on 2D PAGE analysis and isobaric tag for relative and absolute quantitation (iTRAQ) has earlier been used to study this fibroblast cell-line model and allowed the discovery of 201 differentially expressed proteins (35). Most of the proteins identified by Pütz et al could be confirmed by our study, although we were, thanks to the higher sensitivity of RNAseq, able to identify as many as 1,357 differentially expressed genes, corresponding to ∼6% of all human genes.…”
Section: Discussionmentioning
confidence: 99%
“…Expression analysis with oligonucleotide microarrays revealed that TRAP1 is one of the target genes elevated by the Myc oncogene (38). TRAP1 was over-expressed in primary human fibroblasts and mouse prostate by SV40-induced malignant transformation (39,40). Various cancer cell lines, including mouse adenocarcinoma, and specimens from human cancer patients also consistently showed over-expression of TRAP1, while it remained undetectable in normal cells and tissues (16,40).…”
Section: Regulation Of Trap1 and Mitochondrial Hsp90mentioning
confidence: 99%